2021
DOI: 10.3389/fpsyt.2021.632252
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Study of the Impact of a Virtual Program to Reduce Stigma Among University Students Toward People With Mental Disorders

Abstract: Stigma toward mental disorders is one of today's most pressing global issues. The Covid-19 pandemic has exacerbated the barriers to social inclusion faced by individuals with mental disorders. Concurrently, stigma reduction interventions, especially those aimed at university students, have been more difficult to implement given social distancing and campus closures. As a result, alternative delivery for programs contributing to stigma reduction is required, such as online implementation. This paper reports the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 77 publications
1
14
0
3
Order By: Relevance
“…The stigma towards mental disorders is one of the most urgent global problems of today ( Rodrí guez-Rivas et al., 2021 ) that generate high levels of social exclusion ( Thornicroft et al., 2007 ) and low quality of life ( Corrigan and Shapiro, 2010 ) that generate feelings of shame and guilt in those affected and worsen depressive symptoms and a high prevalence of suicidal ideation and behaviors is associated. Because medical students have high levels of stigma, this not only affects them, but also determines the care they give to patients affected by mental illness ( Rodríguez-Rivas, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stigma towards mental disorders is one of the most urgent global problems of today ( Rodrí guez-Rivas et al., 2021 ) that generate high levels of social exclusion ( Thornicroft et al., 2007 ) and low quality of life ( Corrigan and Shapiro, 2010 ) that generate feelings of shame and guilt in those affected and worsen depressive symptoms and a high prevalence of suicidal ideation and behaviors is associated. Because medical students have high levels of stigma, this not only affects them, but also determines the care they give to patients affected by mental illness ( Rodríguez-Rivas, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the current global covid-19 pandemic, interventions that can be applied given social distancing are vital. In this regard, a controlled study conducted on the effectiveness of an online multi-component program in reducing stigma toward mental illness found that online programs can play a role in reducing stigma toward mental disorders [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As 3 of the studies included more than 1 scale that assessed levels of stigma [ 11 , 22 , 31 ], we conducted an analysis that combined them into a single effect size. In those cases, we followed the methodology suggestion for complex data structures [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although direct face-to-face contact with people with mental illness has been shown to be a key component of successful stigma reduction programs, their implementation in virtual learning and innovative spaces is recent [ 10 ]. In the last years, several authors have shown that innovative technology-based interventions have had a great impact on the reduction of stigma toward people with mental illness, mainly due to its adaptability to different contexts and age ranges [ 11 ]. Among this type of interventions, the use of video games has been highlighted as an effective tool to reduce anxious and depressive symptomatology in patients, and has been useful to reduce misconceptions and stigmatization about severe mental illnesses, such as schizophrenia or bipolar disorder [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation